Pengaruh Kualitas Produk, Desain Produk, Promosi Terhadap Keputusan Pembelian Pada PT Bentoro Adisandi Ivena Batam - Elyn Stefanny; Suhardi (Komunitas Dosen Indonesia, 2023)
This research can provide the objective of analyzing how product quality, product design and promotion can have a partial or simultaneous influence on purchasing decisions at PT Bentoro Adisandi Ivena. This type of research can use this type of research which is a quantitative research method, the population used is consumers in June 2022 with 155 respondents in this survey. Thus the sampling technique to be used is saturated sampling. Data sources can use primary data as well as secondary data. In the data analysis method, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis (R2), partial test and simultaneous test can be used. The results of the study can show that product quality has partially given a positive and significant relationship to purchasing decisions. Furthermore, product design has partially given a positive and significant relationship to purchasing decisions. Furthermore, promotion partially has given a positive and significant relationship to purchasing decisions. As well as the simultaneous results which can show that product quality, product design and promotion have given a positive and significant relationship to purchasing decisions at PT Bentoro Adisandi Ivena